Axially loaded capacity of alternatively strengthened cold-formed channel columns with CFRP. (January 2018) - Amoush, Essam A.; Ghanem, Mohamed A.
Abstract: Carbon fiber is considered as a newly alternative technique used in enhancing the strength and behavior of different members in many steel structures applications. In this research, an experimental study for strengthening of cold-formed lipped channel columns using carbon fiber reinforced polymers (CFRP) is conducted. Twelve cold-formed columns specimens with different parametric variables are chosen. Different variables such flange width-thickness, web depth-thickness ratios for un-strengthened, partially, and fully strengthened short columns, as well as overall slenderness ratios for partially strengthened short and medium columns are selected. The cold-formed column specimens were tested under axial compression load. A finite element model is developed using ANSYS program to simulate and verify the laboratory tested specimen's results. The developed FE model includes both geometric and material nonlinearities. The strengthened columns behavior along with local, distortion and rupture failure modes are investigated. A comparison between experimental and finite elements as well as the direct strength method (DSM) axial capacities, is carried out. Finite element and direct strength method results are comparable with the experimental results. Highlights: The alternatively strengthened columns behavior along with local, distortion and rupture failure modes are investigated. A finite element program ANSYS is used to simulate and verify the experimentally tested specimens. Finite element and direct strength method results are comparable with the experimental results.